Map of the heart [compact disc, unabridged] : a novel - Wiggs, Susan (Harper Audio, 2017)
Susan Wiggs returns with a deeply emotional and atmospheric story of love and family, war and secrets that moves back and forth across time, from the present day to World War II France.